1994
DOI: 10.1104/pp.106.2.703
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Short- and Long-Term Changes in Gene Expression Caused by Low Water Potential in Potato (Solanum tuberosum) Cell-Suspension Cultures

Abstract: To dissect the cellular response to water stress and compare changes induced as a generalized response with those involved in tolerance/acclimation mechanisms, we analyzed changes in two-dimensional electrophoretic patterns of in vivo [35S]methionine-labeled polypeptides of cultured potato (Solanum tuberosum) cells after gradual and long exposure to polyethylene glycol (PEG)- mediated low water potential versus those induced in cells abruptly exposed to the same stress intensity. Protein synthesis was not inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 28 publications
2
28
1
Order By: Relevance
“…Protein response depends on the type of stress: Leone et al [98] showed that the protein response fo Solanum tuberosum cell suspensions abruptly submitted to low water potential was different from the response to gradual decrease of the water potential. ABA also induced most of proteins induced by abrupt treatment.…”
Section: Candidate Proteins For Drought Tolerancementioning
confidence: 99%
“…Protein response depends on the type of stress: Leone et al [98] showed that the protein response fo Solanum tuberosum cell suspensions abruptly submitted to low water potential was different from the response to gradual decrease of the water potential. ABA also induced most of proteins induced by abrupt treatment.…”
Section: Candidate Proteins For Drought Tolerancementioning
confidence: 99%
“…Potato (Solanum tuberosum 'DesirĂše') cell cultures were generated, maintained, and gradually or abruptly exposed to 20% (w/v) PEG 8000 as described previously (Leone et al, 1994;Ambrosone et al, 2011). Arabidopsis (Arabidopsis thaliana) MM2D cells (ecotype Landsberg erecta) were maintained as described (Menges and Murray, 2002) in continuous dark conditions.…”
Section: Plant Materials and Stress Treatmentsmentioning
confidence: 99%
“…Our data indicated that water stress imposed gradually is compatible with active cellular growth (Leone et al 1994a), primarily due to restored normal protein synthesis (Leone et al 1994b), proline and polyamine accumulation (Scaramagli et al 2000) and changes in membrane composition and fluidity (Leone et al 1996). Although a cell system is not representative of the whole plant's response, the data indicate that external conditions used to impose water stress are critical to infer whether the observed transcriptional changes are associated to cellular damage rather than to the plant's ability to sustain acceptable growth at otherwise non permissive water status.…”
Section: Introductionmentioning
confidence: 72%